2011
DOI: 10.1089/thy.2010.0449
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Tests in Persons with Occupational Exposure to Fipronil

Abstract: This study did not show that chronic fipronil exposure was associated with an increase of thyroid function test abnormalities. But, despite the fact that fipronil exposure in rats has been associated with increased serum TSH, fipronil sulfone concentrations were negatively correlated with serum TSH concentrations in fipronil-exposed workers, raising the possibility that fipronil has a central inhibitory effect on TSH secretion in humans. Close occupational medical surveillance, therefore, appears to be require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
0
30
2
Order By: Relevance
“…The median from the occupational exposure study was calculated from the mean (μ) and standard deviation (σ) provided via a method by Pleil et al (2014) where the geometric mean is used to estimate the median which is equal to μ/[1 + 0.5 × (σ/μ) 2 ]. Interestingly, the maximum concentration observed in this study (3.9 ng/mL) was only slightly less than the calculated median of 5.2 (GSD = 2.4) ng/mL for the occupationally exposed workers (Herin et al, 2011) (see Fig. 2), where error is represented in terms of the geometric standard deviation (GSD).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The median from the occupational exposure study was calculated from the mean (μ) and standard deviation (σ) provided via a method by Pleil et al (2014) where the geometric mean is used to estimate the median which is equal to μ/[1 + 0.5 × (σ/μ) 2 ]. Interestingly, the maximum concentration observed in this study (3.9 ng/mL) was only slightly less than the calculated median of 5.2 (GSD = 2.4) ng/mL for the occupationally exposed workers (Herin et al, 2011) (see Fig. 2), where error is represented in terms of the geometric standard deviation (GSD).…”
Section: Discussioncontrasting
confidence: 66%
“…The dotted line represents the median calculated from an occupational exposure study (Herin et al, 2011; Pleil et al, 2014). * n = 96, four samples were excluded due to insufficient volume.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other signs of toxicity were observed including convulsions, head nodding and muscles twitching (Hamernik 1998; Woodward 2012). Herin et al (2011) assessed serum concentrations of thyroid-stimulating hormone (TSH), fipronil and fipronil sulfone in 159 workers in a factory manufacturing fipronil-containing veterinary drugs. They found a significant positive correlation between exposure and fipronil/fipronil sulfone concentration in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…However, nowadays there is greater awareness of the risk of long term effects attributable to frequent exposure to doses of low concentrate pesticides (Kapoor et al 2011; Herin et al 2011). Also, new studies revealed the close relationship between the chronic health effects that become apparent at a given moment in life and the prolonged or repeated exposure to low doses of pesticides at earlier ages (Winans et al 2011; Bailey et al 2011).…”
Section: Introductionmentioning
confidence: 99%